2019
DOI: 10.1002/jcp.28243
|View full text |Cite
|
Sign up to set email alerts
|

Autophagic regulation of platelet biology

Abstract: Platelets, developed from megakaryocytes, are characterized by anucleate and short‐life span hemocyte in mammal vessel. Platelets are very important in the cardiovascular system. Studies indicate the occurrence of autophagy platelets and megakaryocytes. Moreover, abnormal autophagy decreases the number of platelets and suppresses platelet aggregation. In addition, mitophagy, as a kind of selective autophagy, could inhibit platelet aggregation under oxidative stress or hypoxic, whereas promote platelet aggregat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“… 18 , 19 In recent years, it has been discovered that platelets can degrade damaged organelles through autophagy mechanisms to maintain intracellular homeostasis, which is similar to nucleated cells. 20 22 In 2014, Feng and colleagues first systematically elucidated the constitutive expression of the autophagy mechanism in human platelets, demonstrating its necessity to maintain the primary function. 7 Additionally, human platelets express components of the ULK1 complex, BECN1-PIK3C3 complex, and autophagosomes, confirming the existence of complete autophagic flux.…”
Section: Discussionmentioning
confidence: 99%
“… 18 , 19 In recent years, it has been discovered that platelets can degrade damaged organelles through autophagy mechanisms to maintain intracellular homeostasis, which is similar to nucleated cells. 20 22 In 2014, Feng and colleagues first systematically elucidated the constitutive expression of the autophagy mechanism in human platelets, demonstrating its necessity to maintain the primary function. 7 Additionally, human platelets express components of the ULK1 complex, BECN1-PIK3C3 complex, and autophagosomes, confirming the existence of complete autophagic flux.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, increased levels of LC3B were observed, which suggested the occurrence of autophagy in the platelets of SFTS patients. Complete autophagic ux, from the formation of autophagosomes to autophagic degradation, is important for the number, size, and activation of platelets and could be a potential therapeutic target for hemorrhagic and thrombosis diseases [55]. Moreover, upregulated autophagy in platelets promotes platelet activation by decreasing hemostasis and thrombus formation [55], which reduce the number of platelets and shorten the lifespan of platelets [56].…”
Section: Discussionmentioning
confidence: 99%
“…Complete autophagic ux, from the formation of autophagosomes to autophagic degradation, is important for the number, size, and activation of platelets and could be a potential therapeutic target for hemorrhagic and thrombosis diseases [55]. Moreover, upregulated autophagy in platelets promotes platelet activation by decreasing hemostasis and thrombus formation [55], which reduce the number of platelets and shorten the lifespan of platelets [56]. Whether SFTSV infection induces complete autophagic ux in human platelets needs to be veri ed.…”
Section: Discussionmentioning
confidence: 99%
“…The latest study showed that P2RY12 receptor inhibits autophagy and reduces cholesterol e uence, promoting VSMC-derived foam cytogenic in advanced atherosclerosis (22). In addition, autophagy has been stated to play an essential role in bleeding and thrombotic diseases by regulating the count and function of PLT, which are the core factors of physiological hemostasia (23). Therefore, it is necessary to conduct clinical or basic experiments to probe the underlying biological functions of these DEARGs.…”
Section: Discussionmentioning
confidence: 99%